2014
DOI: 10.1016/j.jenvrad.2013.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Effective Half-Life of Caesium-137 in Various Environmental Media at the Savannah River Site

Abstract: During the operational history of the Savannah River Site (SRS), many different radionuclides have been released from site facilities into the SRS environment. However, only a relatively small number of pathways, most importantly (137)Cs in fish and deer, have contributed significantly to doses and risks to the public. The "effective" half-lives (Te) of (137)Cs (which include both physical decay and environmental dispersion) in Savannah River floodplain soil and vegetation and in fish and white-tailed deer fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Shown in the gamma overflight map of SRS (Figure 3-6), much of this cesium was retained in the clayey soils/sediments of the L3R, SC, PB, and FM site streams. It has been shown that the "effective" half-life (which include both physical decay and environmental dispersion) of cesium-137 in SRS floodplain soil/sediment is about 17 years (Paller, Jannik, and Baker, 2014). So, after 3 effective half-lives since the 1960's releases, about 1/8 th of the original cesium remains in the stream beds and swamps.…”
Section: Sediment Discussionmentioning
confidence: 99%
“…Shown in the gamma overflight map of SRS (Figure 3-6), much of this cesium was retained in the clayey soils/sediments of the L3R, SC, PB, and FM site streams. It has been shown that the "effective" half-life (which include both physical decay and environmental dispersion) of cesium-137 in SRS floodplain soil/sediment is about 17 years (Paller, Jannik, and Baker, 2014). So, after 3 effective half-lives since the 1960's releases, about 1/8 th of the original cesium remains in the stream beds and swamps.…”
Section: Sediment Discussionmentioning
confidence: 99%
“…To determine the spatial variation of soil 137 Cs prior to the CPPF in 2019, we applied the approach used by Ager et al (2019). Specifically, we used a point-based dataset of soil of 137 Cs from 1995 (Kashparov et al 2017) and then used these 1995 levels to estimate 2019 levels using a half-life of 17 years (Paller et al 2014; Eq. 3):…”
Section: Methodsmentioning
confidence: 99%
“…where A is 2019 contamination and A 0 is 1995 deposition values, DP (the number of years since the inventory was taken) is 24 years (1995-2019) mapping, and Te (the effective half-live) is 17 years (as suggested by Paller et al 2014). We used the empirical Bayesian kriging (EBK) interpolation method within ArcMap 10.3.1 to estimate soil 137 Cs for 2019 across the area affected by the CPPF.…”
Section: Methodsmentioning
confidence: 99%
“…Wildlife living near these areas are then exposed to radionuclides, and research has found that their tissues contain higher activity concentrations of these anthropogenic contaminants than wildlife living in other areas (Connelly and Markham 1983; Oldenkamp et al 2017). Because of the long half‐life of some radionuclides, such as radiocesium (Cs 137 ), contamination effects can persist in the environment for decades or more (Paller et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The radionuclide Cs 137 can accumulate in the tissues of wildlife and can pose health risks to exposed wildlife and human consumers. When consumed, Cs 137 acts as an analog to potassium, allowing it to accumulate in muscle and other soft tissues of animals, which then act as a vector of exposure to predators and human consumers of meat (Paller et al 2014). Potassium has been found to accumulate in higher concentrations in “red” (e.g., leg) muscle compared with “white” (e.g., breast) muscle (Chutkow 1973), indicating that Cs 137 activity levels may also vary among muscle types in birds.…”
Section: Introductionmentioning
confidence: 99%